2012
DOI: 10.1080/00028487.2012.711263
|View full text |Cite
|
Sign up to set email alerts
|

Age, Growth, Survival, and Maturity of Lake Trout Morphotypes in Lake Mistassini, Quebec

Abstract: Life history characteristics (age, growth, survival, and maturity) were compared between the deepwater “humper” and shallow‐water “lean” forms of lake trout Salvelinus namaycush in Lake Mistassini, Quebec, to determine whether the two morphotypes may represent resource polymorphism. Lake trout were sampled using graded‐mesh (range = 51–114 mm stretch) gill nets set in deep and shallow waters. Humpers were typically caught in deep waters (>50 m) and averaged 474 mm TL (range = 389–616 mm) and 852 g in weight (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 65 publications
1
43
0
Order By: Relevance
“…Dubois and Lagueux (1968) documented the age and size of lake trout from unknown localities. Zimmerman et al (2007) identified two forms that differed in age, growth, and maturity (Hansen et al 2012) in a small area of the lake. Most recently, Marin et al (2016) sampled the entire lake and used morphological and DNA analyses to determine that Mistassini harbors at least five weakly differentiated subpopulations of sympatrically occurring lake trout with striking phenotypic variation, including differences in body size, coloration, and to a lesser extent, body depth, caudal peduncle size, eye position, and head shape.…”
Section: Introductionmentioning
confidence: 99%
“…Dubois and Lagueux (1968) documented the age and size of lake trout from unknown localities. Zimmerman et al (2007) identified two forms that differed in age, growth, and maturity (Hansen et al 2012) in a small area of the lake. Most recently, Marin et al (2016) sampled the entire lake and used morphological and DNA analyses to determine that Mistassini harbors at least five weakly differentiated subpopulations of sympatrically occurring lake trout with striking phenotypic variation, including differences in body size, coloration, and to a lesser extent, body depth, caudal peduncle size, eye position, and head shape.…”
Section: Introductionmentioning
confidence: 99%
“…From full-body photographs (Muir et al, 2012b), most fish were assigned to a morph using a combination of statistical analysis of head and body measures and visual assignment, as described by Muir et al (2014). However, for some fish, statistical assignments differed between head and body measures, and visual consensus was not reached, so these fish were classified by visual comparison to the library of statistical and visual assignments (Hansen et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Sagittal otoliths were used because they have been validated for age estimation of lake charr to an age of at least 50 years (Campana et al, 2008). One otolith from each fish was embedded in epoxy, and a thin transverse section (400 lm) was cut, mounted on glass slides, polished, and photographed for age and growth assessment (Hansen et al, 2012). Annuli were counted by three independent readers using criteria described by Casselman & Gunn (1992), and specimens were excluded from analysis if the coefficient of variation (CV) of age estimates was more than 5% (Campana, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations